A model for investigating the temperature of trochoidal machining. (18th May 2020) - Deng, Qi; Chen, Zezhong C.; Chang, Zhiyong; Shen, Ronghan; Zhou, Yimeng
ABSTRACT: In this paper, a model of estimating the cutter temperature during trochoidal machining is proposed. First, the trochoidal tool path is expressed by two parameters, trochoidal radius r, and trochoidal step c . Second, the engagement during trochoidal milling is analyzed, and one cycle of trochoidal tool path is divided into two phases. According to the characteristics of two phases, an equation that describes the heat input is derived. Then, the heat diffusion equation, which describes temperature of the cutter, is acquired by thermal balance analysis and is solved numerically. Finally, the temperature of both trochoidal and conventional end milling are figured out based on the proposed approach. The results show that the trochoidal machining has a remarkable advantage on lowering the temperature of the cutter, which will certainly prolong the tool life. And, this is consistent with the earlier experimental researches of many scholars.